2016
DOI: 10.24036/02016536554-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Kepercayaan Diri dan Kecerdasan Emosi terhadap Komunikasi Interpersonal Siswa serta Implikasinya dalam Pelayanan Bimbingan dan Konseling

Abstract: PENDAHULUANTugas perkembangan merupakan suatu tugas yang muncul pada periode tertentu dalam rentang kehidupan individu. Tugas perkembangan berkaitan dengan sikap, perilaku, dan keterampilan yang sebaiknya dimiliki oleh setiap individu sesuai dengan fase atau usia perkembangannya. William Kay (dalam Yusuf, 2009:72) menjelaskan bahwa salah satu tugas perkembangan remaja adalah mengembangkan kemampuan berkomunikasi dan belajar berinteraksi dengan teman sebaya atau orang lain, baik secara individual maupun berke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 1 publication
1
7
0
17
Order By: Relevance
“…And services that could be implemented to improve and develop interpersonal communication is information, orientation, guidance and counseling group of individuals. This is in accordance with the research conducted by Sahputra, Syahniar & Marjohan (2016) revealed that the information services, orientation, guidance and counseling group of individuals who applied to the students to effectively improve communications interpersonal students.…”
Section: Interpersonal Communication Regression Coefficient Test On Psupporting
confidence: 91%
“…And services that could be implemented to improve and develop interpersonal communication is information, orientation, guidance and counseling group of individuals. This is in accordance with the research conducted by Sahputra, Syahniar & Marjohan (2016) revealed that the information services, orientation, guidance and counseling group of individuals who applied to the students to effectively improve communications interpersonal students.…”
Section: Interpersonal Communication Regression Coefficient Test On Psupporting
confidence: 91%
“…That is to say, the higher the confidence the better the interpersonal communication. Conversely, if the confidence is low it results in low interpersonal communication (Sahputra, 2016). This finding was obtained based on a series of data analyzes which showed that self-confidence to a large extent contributes to interpersonal communication by 19.6%.…”
Section: The Contribution Of Self Confidence To Interpersonal Communimentioning
confidence: 97%
“…Dengan demikian, individu yang memiliki kecerdasan emosi yang baik, apabila memiliki hubungan sosial yang matang, mudah berteman, jenaka, tidak mudah takut atau gelisah, mampu menyesuaikan diri dengan beban stres, serta memiliki kemampuan besar untuk melibatkan diri dengan orang orang atau permasalahan, untuk mengambil tanggung jawab, dan memiliki pandangan moral. Salah satu keberhasilan dalam berkomunikasi adalah adanya rasa percaya diri (Dika, Syahniar & Marjohan, 2016). Hal ini menandakan bahwa dalam berkomunikasi siswa dapat diterima oleh orang lain, karena keberhasilan komunikasi sebagian besar dipengaruhi oleh kecerdasan emosi.…”
Section: Pembahasan Kecerdasan Emosiunclassified